Total knee arthroplasty combined with simultaneous open reduction and internal fixation in the treatment of knee osteoarthritis with patellar fracture: a case report and review of the literature - DongFeng Cai; JiMo Li; Song Hong (Journal of Medical Case Reports)
Abstract Background Patients with severe knee osteoarthritis combined with patellar fracture are rare, and it is unclear whether single-stage surgery affects the enhanced recovery after surgery. Case presentation This case report describes two patients of Han nationality. A 69-year-old male patient was previously diagnosed with severe knee osteoarthritis of the left knee joint and was treated conservatively with long-term oral nonsteroidal antiinflammatory drugs and intraarticular injection of sodium hyaluronate. He was hospitalized for acute left knee injury owing to a fall from a height. He was diagnosed with knee osteoarthritis of the left knee joint and patellar fracture. Another 74-year-old female patient was previously diagnosed with severe knee osteoarthritis, long-term oral nonsteroidal antiinflammatory drugs and topical Chinese medicine to relieve the pain. A month ago, she fell down the stairs and fractured the patella in her left knee, she was diagnosed with severe left knee osteoarthritis combined with an old left patella fracture. Both patients were successfully treated by single-stage primary total knee arthroplasty and fixation of the patellar fracture. They both carried out early functional exercise normally and successfully achieved enhanced recovery. Conclusion Successful single stage total knee replacement with patella management can not only reduce the number of operations, but also enable patients to achieve rapid postoperative recovery. However, single stage may increase the risk of local surgical complications. Therefore, for most patients, especially those with low risk of anesthesia related complications, standard of treatment remains first fixing the patellar fracture and when the fracture is healed proceed with the total knee arthroplasty.